The Predictive Role of Self-Compassion on Entrapment in Turkish University Students - Akin, Ahmet; Sakarya University, Faculty of Education, Department of Psychological Counselling and Guidance (2015)
The purpose of this study is to examine the predictive role of self-compassion on entrapment. Participants were 338 university students (185 women, 153 men; M age = 20.5 yr.). In this study, the Self-compassion Scale and the Entrapment Scale were used. The relationships between self-compassion and entrapment were examined using correlation analysis and multiple regression analysis. In correlation analysis, self-kindness, common humanity, and mindfulness factors of self-compassion were found negatively and self-judgment, isolation, and over-identification factors of self-compassion were found positively related to entrapment. According to regression results, entrapment was predicted positively by self-judgment, isolation, and over-identification. Further self-kindness and common humanity predicted entrapment in a negative way. Self-compassion has explained 50% of the variance in entrapment. The results were discussed in the light of the related literature and dependent recommendations to the area were given.